MISKONSEPSI PEMBELAJARAN ILMU PENGETAHUAN ALAM (IPA) KELAS V DI SEKOLAH DASAR - Prastika, Anggraeni Dyah (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
The research about the misconception of science teaching-learning of fifth grade in Elementary School aims to find out the misconception found in Science books, misconception during science teaching-learning process, determine the causes of the misconception and the percentage of the misconception of the books used by teachers in the class during the science learning for the fifth graders. The method used in this research was a descriptive method with the quantitative and qualitative design. The quantitative method was aimed at measuring the numbers of misconception of the books used by teachers during the science teaching and learning process in class V. Qualitative method was by interview and observation technique to dig the teachers’ misconception in the teaching-learning process. The object of this research was the book of science for the fifth graders and the subject was some teachers of the fifth grades of elementary schools in Purwokerto Utara. The result of the research showed that there was a misconception of the books used by the teachers, therefore this misconception was brought to the class during the teaching-learning process. The factors causing this misconception were the wrong textbooks, the teacher’s less material mastery, and science material understanding, the teacher’s teaching methodology was always monotonous. The percentage of the book misconception was 5,45%, this number belonged to very low category, therefore it needed some improvement by selecting the books